Distribution of 45S and 5S rDNA sites in 23 species of Eleocharis (Cyperaceae) - Maximiano da Silva, Carlos Roberto [UNESP]; Quintas, Carolina Cristina; Laforga Vanzela, Andre Luis (Springer, 2010)
Studies of rDNA location in holocentric chromosomes of the Cyperaceae are scarce, but a few reports have indicated the occurrence of multiple 45S rDNA sites at terminal positions, and in the decondensed state of these regions in prometaphase/metaphase. To extend our knowledge of the number 45S and 5S rDNA sites and distribution in holocentric chromosomes of the Cyperaceae, 23 Brazilian species of Eleocharis were studied. FISH showed 45S rDNA signals always located in terminal regions, which varied from two (E. bonariensis with 2n = 20) to ten (E. flavescens with 2n = 10 and E. laeviglumis with 2n = 60). 5S rDNA showed less variation, with 16 species exhibiting two sites and 7 species four sites, preferentially at terminal positions, except for four species (E. subarticulata, E. flavescens, E. sellowiana and E. geniculata) that showed interstitial sites. The results are discussed in order to understand the predominance of terminal rDNA sites, the mechanisms involved in the interstitial positioning of 5S rDNA sites in some species, and the events of amplification and dispersion of 45S rDNA terminal sites.
Keywords: FISH; Holocentric chromosomes; rDNA distribution; DNA amplification